Citizens' intent and behavior towards recycling in the municipality of Kavala - Paraskevas Kechagias; Efstathios Dimitriadis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study examines the factors that tend to affect citizens intent and behavior towards recycling. There are several key factors that can influence this behavior, such as Individual perception and behavior towards recycling as well as the spatial planning of recycling bins and the recycling culture. Design/methodology/approach: Taking these variables into account a quantitative survey was carried out on a sample of 307 people in the municipality of Kavala from June 2018 to June 2019. The data were gathered through the use of a structured questionnaire implemented with the SPSS 20.0 and the techniques applied were Correlation Analysis, Regression analysis and ANOVA analysis. Finding: The results of the survey showed that "Recycling Behavior" and "Recycling Culture" are the factors that affect the behavior towards recycling the most according to the citizens of Kavala. On the other hand 'Spatial planning of recycling bins' seems to be indifferent to the participants while 'Individual perception about recycling' is the least agreeable factor. Research limitations/implications: One of the most basic and uncontrolled constraints is the objectivity of the responses given by the individuals who completed the questionnaires. It is worth mentioning the negative reaction of many male respondents when they were informed about the subject of the survey. In a way, the researcher tried to obtain the most objective answers possible through clarifying questions. In addition, some of the difficulties faced by the researcher were the negative responses about answering the questionnaire using as an excuse the lack of time, while individual cases of respondents (10) refused to participate in the research because its issue was not of their concern or interest. Originality/value: This survey shows citizens' behavior towards recycling following the implementation of recycling measures by the Municipality of Kavala.
Keywords: Q50; Q53; Q56; Q58; 330; Recycling; behavior; attitude